2022
DOI: 10.1177/14788047221135343
|View full text |Cite
|
Sign up to set email alerts
|

Game-based learning as a gateway for promoting financial literacy – how games in economics influence students’ financial interest

Abstract: The teaching of financial literacy through game-based approaches is legitimized by the ability of game-based learning (GBL) to simulate financial decisions that young people have not yet encountered in their lives due to limited legal capacity and economic dependence on the parental home. Although results on the general effectiveness of games are already available, the question about for which students GBL is effective in teaching financial literacy has not yet been researched in depth. Based on pedagogical in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…Hence, motivation and the mode of offering are vital to engaging students in financial content. Platz and Jüttler (2022) found that motivated students in finance have a positive link to the game experience. The success of financial education depends on "learning from doing".…”
Section: Motivation To Engage the Contentmentioning
confidence: 99%
“…Hence, motivation and the mode of offering are vital to engaging students in financial content. Platz and Jüttler (2022) found that motivated students in finance have a positive link to the game experience. The success of financial education depends on "learning from doing".…”
Section: Motivation To Engage the Contentmentioning
confidence: 99%
“…However, Morgan et al (2019) provide a complete definition, focusing not only on knowledge but also on critical awareness, pointing out four fundamental elements: (1) knowledge of digital financial products and services (payments, asset management, or financing through digital means); (2) awareness of digital financial risks (online fraud and cybersecurity risks such as phishing, pharming, spyware, and SIM-card swapping); (3) control of these (knowing how to protect yourself from the risks derived from the use of digital financial services); and (4) knowledge of consumer rights and fraud-redress procedures (in the case of being a victim of fraud or loss, knowing your rights, where to go for help, and how to obtain redress). These contributions to digital financial literacy allow progress in developing specific training programs and evaluation tools (Lyons & Kass-Hanna, 2021; Platz & Jüttler, 2022).…”
Section: Theoretical Backgroundmentioning
confidence: 99%